The Surgeon's Role in the Opioid Crisis: A Narrative Review and Call to Action - Shadbolt, Cade; Abbott, J. Haxby; Camacho, Ximena; Clarke, Philip; Lohmander, L. Stefan; Spelman, Tim; Sun, Eric C.; Thorlund, Jonas B.; Zhang, Yuting; Dowsey, Michelle M.; Choong, Peter F. M. (Frontiers in Surgery, 2020)
Over the past two decades, there has been a sharp rise in the use of prescription opioids. In several countries, most notably the United States, opioid-related harm has been deemed a public health crisis. As surgeons are among the most prolific prescribers of opioids, growing attention is now being paid to the role that opioids play in surgical care. While opioids may sometimes be necessary to provide patients with adequate relief from acute pain after major surgery, the impact of opioids on the quality and safety of surgical care calls for greater scrutiny. This narrative review summarizes the available evidence on rates of persistent postsurgical opioid use and highlights the need to target known risk factors for persistent postoperative use before patients present for surgery. We draw attention to the mounting evidence that preoperative opioid exposure places patients at risk of persistent postoperative use, while also contributing to an increased risk of several other adverse clinical outcomes. By discussing the prevalence of excess opioid prescribing following surgery and highlighting significant variations in prescribing practices between countries, we note that there is a pressing need to optimize postoperative prescribing practices. Guided by the available evidence, we call for specific actions to be taken to address important research gaps and alleviate the harms associated with opioid use among surgical patients.